Potentialities of Shared Management for a Sustainable Society - Brito, Renato de Oliveira; Síveres, Luiz (European Journal of Sustainable Development, 2014)
The aim of this study was to outline the factors that contribute to a feeling of motivation on the part of the school community and to encouragement of its participation in issues related to the school routine. We specifically sought to understand whether the management framework adopted by the school, the object of this study, contributes to the active participation of the community to facilitate the implementation of projects related to environmental education for a sustainable society. The methodology of this qualitative research was a review of the literature and application of questionnaires as data collection instruments. We concluded that the factors that contribute to the school community participating in the elaboration and implementation of the educational policy project of the school, the object of this study, lead to its shared management model favoring the implementation of educational projects for a sustainable society. Keywords: Shared management. Environmental Education. School and community relationship.